Mechanical behavior analysis of buried pipeline under stratum settlement caused by underground mining. (December 2020) - Yu, Cheng; Han, Chuanjun; Xie, Rui; Wang, Lin
Abstract: The stratum settlement caused by underground mining is one of the main geological disasters that threaten and damage buried pipelines. Therefore, the mechanical behavior of buried pipe under stratum settlement is investigated in this paper. Effects of pipeline parameters, mining area parameters and inclination directions of mining area on mechanical behavior of the buried pipeline are discussed. The results show that the maximum Von Mises stress and the maximum vertical displacement of pipeline are located in the middle of the pipeline during the mining process. As the excavation length increases, the Von Mises stress, the circumferential strain and vertical displacement increase. However, there is only stress concentration in the pipeline, and does not appear yield deformation. The vertical displacement of the pipeline is much greater than the horizontal displacement. The maximum stratum displacement appears on the upper surface of the mining area and it is stratum settlement. In addition, as the diameter-thickness ratio, buried depth, surrounding soil thickness of the pipeline and the height and the width of mining area increase, the maximum Von Mises stress, the circumferential strain and maximum vertical displacement of the pipeline increase, but they decrease with the increase of the buried depth of mining area. Whether the mining area is horizontal inclination or longitudinal inclination, the maximum Von Mises stress and maximum vertical displacement of pipeline are located in the middle of the pipeline. The maximum Von Mises stress, the circumferential strain and vertical displacement of pipeline decrease with the increase of the inclination angle. However, for the mining area of longitudinal inclination, the pipeline would produce horizontal displacement, the horizontal displacement of the pipeline increases with the increase of longitudinal inclination angle, and the position of the maximum strain of the pipe appears to shift. For the mining area of horizontal inclination, with the increase of horizontal inclination angle, the right side of vertical displacement curves approximately overlap, but the left side separates from each other. Highlights: The strain changes of buried pipelines under stratum settlement caused by underground mining are studied. The maximum Von Mises stress and vertical displacement of pipeline are located in the middle of the pipeline when mining. For the mining area of longitudinal inclination, the pipe would produce horizontal displacement. For the mining area of longitudinal inclination, the position of the maximum strain has shifted. For the mining area of horizontal inclination, the vertical displacement change on only one side of the pipe is obvious.